Waste management, public participation, Sabah Introduction - Mohammad Tahir Mapa (2011)
The increase in world population will cause impact on solid waste. This impact is mostly felt by local authorities. Therefore, cooperation with other stakeholders is essential to ensue that municipal solid waste plan works perfectly. Among the most important element is the involvement of public society. This study aimed to introduce waste recycling in the city. In this study, questionnaire was used to achieve the objectives stated. The study found that residents in the study area are not satisfied on the services provided by the municipal. Furthermore, people in the study area „refuse? to engage actively in the recycling activities. This is because they are not motivated and did not realize the benefits to the environment. Thus, the provision of adequate infrastructure is essential. It can help people to change lifestyles to a more environmentally friendly. Municipal level planning should emphasize methods to increase motivation to carry on recycling. Keywords: Waste management, public participation, Sabah Introduction The increase in the world population and industrialisation of more cities mean that managing the waste produced by city inhabitants is a complex issue due not only to the increasing volume of waste through high material consumption but also to the changing characteristics of waste and uncertainty regarding uncontrolled dumping and overflowing landfills. This is especially significant for many cities in the developing world, where populations and economies are rapidly expanding but the infrastructure necessary to manage the ensuing problems remains inadequate. Over the last century, the world has seen a considerable increase in amounts of waste discharged into the environment. The high generation of solid waste has been identified as a factor contributing to the world environmental problems, and the decrease in suitable landfill sites and scarcity of natural resources is creating greater demand for remanufacturing and reuse. Waste creates environmental consequences such as